Early evolution and ecology of camouflage in insects - Pérez-de la Fuente, Ricardo (National Academy of Sciences, 2012)
Taxa within diverse lineages select and transport exogenous materials for the purposes of camouflage. This adaptive behavior also occurs in insects, most famously in green lacewing larvae who nestle the trash among setigerous cuticular processes, known as trash-carrying, rendering them nearly undetectable to predators and prey, as well as forming a defensive shield. We report an exceptional discovery of a green lacewing larva in Early Cretaceous amber from Spain with specialized cuticular processes forming a dorsal basket that carry a dense trash packet. The trash packet is composed of trichomes of gleicheniacean ferns, which highlight the presence of wildfires in this early forest ecosystem. This discovery provides direct evidence of an early acquisition of a sophisticated behavioral suite in stasis for over 110 million years and an ancient plant–insect interaction.